2018
DOI: 10.1038/s41598-018-22872-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of innate immune cell subsets across spatial and temporal scales in an EAE mouse model

Abstract: In both multiple sclerosis and its model experimental autoimmune encephalomyelitis (EAE), the extent of resident microglia activation and infiltration of monocyte-derived cells to the CNS is positively correlated to tissue damage. To address the phenotype characterization of different cell subsets, their spatio-temporal distributions and contributions to disease development we induced EAE in Thy1-CFP//LysM-EGFP//CD11c-EYFP reporter mice. We combined high content flow cytometry, immunofluorescence and two-photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 46 publications
2
59
0
Order By: Relevance
“…To test this, we examined the lumbar spinal cord ventral horn because it is the residential address of lower motor neurons and interneurons, both indispensable for normal functioning of hindlimbs [46,47]. Further, neutrophils are more abundant in the ventral spinal cord than in lateral areas [48]. Neutrophil-specific Cxcr2 ablation markedly improved spinal cord neuron morphology, as measured by neuron soma size and dendritic density, at late-phase EAE.…”
Section: Discussionmentioning
confidence: 99%
“…To test this, we examined the lumbar spinal cord ventral horn because it is the residential address of lower motor neurons and interneurons, both indispensable for normal functioning of hindlimbs [46,47]. Further, neutrophils are more abundant in the ventral spinal cord than in lateral areas [48]. Neutrophil-specific Cxcr2 ablation markedly improved spinal cord neuron morphology, as measured by neuron soma size and dendritic density, at late-phase EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, my team recently reported that neutrophils invade the spinal cord before monocyte-derived macrophages in EAE mice (Caravagna et al, 2018). But if it is correct, as Tsutsui et al (2018) conclude, that decreased production of CXCL2 by macrophages in TRPM2-KO mice re-duces neutrophil infiltration, neutrophils would have to enter the spinal cord after monocyte-derived macrophages.…”
Section: Review Of Tsutsui Et Almentioning
confidence: 98%
“…Nevertheless, hematopoieticderived myeloid cells including neutrophils, monocytes, and DCs are likely to be important mediators of Dectin-1 function in EAE. Neutrophils in particular may be involved, given their abundance 40 , protective functions 41 , and localization at sites of demyelination and axonal damage in the SC parenchyma during EAE 63, 64, 65 66, 67 . While the role of neutrophils in MS remains elusive, multiple studies suggest involvement of neutrophils, or granulocytic myeloid-derived suppressor cells (G-MDSCs), in both MS and EAE 41,68,69,70,71,72,73,74,75,76 .…”
Section: Studies On Clrs In Eae and Related Models Have Mostly Focusementioning
confidence: 99%